A Spiritual Model Of Good Deeds According To Imam Al-ghazali - Mohd Rosmizi Abd Rahman; Mohamed Mihlar Abdul Muthaliff; Muhammad Khairi Mahyuddin; Ahmad Najaa' Mokhtar; Yuseri Ahmad (Center for Promoting Ideas, USA, 2024)
Non-Indexed Publication